Introducing fluorescence resonance energy transfer‐based biosensors for the analysis of cAMP‐PKA signalling in the fungal pathogen Candida glabrata. (19th June 2018) - Demuyser, Liesbeth; Van Genechten, Wouter; Mizuno, Hideaki; Colombo, Sonia; Van Dijck, Patrick
Abstract: The cyclic adenosine monophosphate‐protein kinase A (cAMP‐PKA) pathway is central to signal transduction in many organisms. In pathogenic fungi such as Candida albicans, this signalling cascade has proven to be involved in several processes, such as virulence, indicating its potential importance in antifungal drug discovery. Candida glabrata is an upcoming pathogen of the same species, yet information regarding the role of cAMP‐PKA signalling in virulence is largely lacking. To enable efficient monitoring of cAMP‐PKA activity in this pathogen, we here present the usage of two FRET‐based biosensors. Both variations in the activity of PKA and the quantity of cAMP can be detected in a time‐resolved manner, as we exemplify by glucose‐induced activation of the pathway. We also present information on how to adequately process and analyse the data in a mathematically correct and physiologically relevant manner. These sensors will be of great benefit for scientists interested in linking the cAMP‐PKA signalling cascade to downstream processes, such as virulence, possibly in a host environment.